The Impact of Genome Triplication on Tandem Gene Evolution in Brassica rapa - Fang, Lu; Cheng, Feng; Wu, Jian; Wang, Xiaowu (Frontiers in Plant Science, 2012)
Whole genome duplication (WGD) and tandem duplication (TD) are both important modes of gene expansion. However, how whole genome duplication influences tandemly duplicated genes is not well studied. We used Brassica rapa, which has undergone an additional genome triplication (WGT) and shares a common ancestor with Arabidopsis thaliana, Arabidopsis lyrata and Thellungiella parvula, to investigate the impact of genome triplication on tandem gene evolution. We identified 2,137, 1,569, 1,751 and 1,135 tandem gene arrays in B. rapa, A. thaliana, A. lyrata and T. parvula respectively. Among them, 414 conserved tandem arrays are shared by the 3 species without WGT, which were also considered as existing in the diploid ancestor of B. rapa. Thus, after genome triplication, B. rapa should have 1,242 tandem arrays according to the 414 conserved tandems. Here, we found 400 out of the 414 tandems had at least one syntenic ortholog in the genome of B. rapa. Furthermore, 294 out of the 400 shared syntenic orthologs maintain tandem arrays (more than one gene for each syntenic hit) in B. rapa. For the 294 tandem arrays, we obtained 426 copies of syntenic paralogous tandems in the triplicated genome of B. rapa. In this study, we demonstrated that tandem arrays in B. rapa were dramatically fractionated after WGT when compared either to non-tandem genes in the B. rapa genome or to the tandem arrays in closely related species that have not experienced a recent whole-genome polyploidization event.